2003
DOI: 10.1161/01.res.0000089255.37804.72
|View full text |Cite
|
Sign up to set email alerts
|

The Obesity-Associated Peptide Leptin Induces Hypertrophy in Neonatal Rat Ventricular Myocytes

Abstract: One of the major manifestations of obesity is increased production of the adipocyte-derived 16-kDa peptide leptin, which is also elevated in heart disease, including congestive heart failure. However, whether leptin can directly alter the cardiac phenotype is not known. We therefore studied the effect of leptin as a potential hypertrophic factor in cultured myocytes from 1-to 4-day-old neonatal rat heart ventricles. Using RT-PCR, we demonstrate that these cells express the short-form (OB-Ra) leptin receptor. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
192
3
10

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(218 citation statements)
references
References 20 publications
13
192
3
10
Order By: Relevance
“…However, recent studies have determined that adipose tissue synthesizes and secretes a number of bioactive molecules that have the ability not only to contribute to the pathogenesis of insulin resistance but also to modulate cardiac remodeling. In addition to resistin, as shown in the present study, leptin has also been reported to promote cardiac hypertrophy [43], [44] through a mechanism involving MAPKs, similar to resistin. In contrast, adiponectin was shown to inhibit cardiac hypertrophy possibly through the activation of AMPK (AMP-activated protein kinase) signaling [45].…”
Section: Discussionsupporting
confidence: 79%
“…However, recent studies have determined that adipose tissue synthesizes and secretes a number of bioactive molecules that have the ability not only to contribute to the pathogenesis of insulin resistance but also to modulate cardiac remodeling. In addition to resistin, as shown in the present study, leptin has also been reported to promote cardiac hypertrophy [43], [44] through a mechanism involving MAPKs, similar to resistin. In contrast, adiponectin was shown to inhibit cardiac hypertrophy possibly through the activation of AMPK (AMP-activated protein kinase) signaling [45].…”
Section: Discussionsupporting
confidence: 79%
“…Until now, most findings have incriminated an overactivity of the sympathetic system per se, induced by circulating factors such as leptin. 4,5 insulin 6 or free fatty acid. 7,8 However, another hallmark factor is the decreased cardiac parasympathetic activity frequently reported in obese patients.…”
Section: Introductionmentioning
confidence: 99%
“…²ñíóþ÷³ óÿâëåííÿ ïðî ïàòîãåíåç ÌÑ óêëàäà-þòüñÿ â ðàìêè òðüîõ òåîð³é [95]. Íàéñòàð³øà ç íèõ -ãëþêîöåíòðè÷íà.…”
Section: роль ліпоцитокінів у патогенезі метаболічного синдромуunclassified
“…Ïîðóøóºòüñÿ äèôåðåí-ö³þâàííÿ ñóáêóòàííèõ ë³ïîöèò³â. ˳ïîãåíåç âèêëèêຠ¿õ ã³ïåðòðîô³þ, à ïîò³ì, ï³ñëÿ âè÷åð-ïàííÿ ðåçåðâ³â äåïîíóþ÷î¿ ôóíêö³¿ ï³äøê³ðíî¿ AEÒ, aeèð ïåðåì³ùóºòüñÿ â àáäîì³íàëüí³ ë³ïîöè-òè [95].…”
Section: роль ліпоцитокінів у патогенезі метаболічного синдромуunclassified
See 1 more Smart Citation